Positional Information—A concept underpinning our understanding of developmental biology. Issue 3 (21st October 2019) - Vargesson, Neil
Abstract: It is now 50 years since Lewis Wolpert published the paper in which he set out the concept of Positional Information to explain how spatial patterns of cellular differentiation are generated. This concept has provided a universal model for pattern formation in embryonic development and regeneration and become part of the fabric of the field of developmental biology. Here I outline how Wolpert devised the concept of Positional Information and describe landmark studies from his lab investigating how Positional Information is specified in the developing chick limb. Key Findings: Outline how Wolpert came up with the concept of Positional Information. Summarise the key findings of Wolperts landmark 1969 paper. Outline the key studies from the Wolpert Lab demonstrating how Positional Information patterns the developing chick limb. Outline how the 1969 paper underpins and influences our understanding of developmental biology today. Detail the key Personnel in a Wolpert Lab Family Tree.